Adjuvant melatonin therapy during exercise prescription in breast cancer survivors on physical and anthropometric parameters, quality of life, and hormonal response. A randomized controlled trial - Ana M. Celorrio San Miguel; Luis M. Cacharro; Gema Santamaría; Manuel Garrosa; Manuel Garrosa; Marta Celorrio San Miguel; Enrique Roche; Enrique Roche; Enrique Roche; Enrique Roche; Evelina Garrosa; Diego Fernández-Lázaro; et al. (Frontiers in Sports and Active Living)
BackgroundBreast cancer has a high prevalence in women during the last years of their life. Exercise is instrumental during this recovery period. Nevertheless, little is known about the effects of combining nutritional supplements with physical activity. Therefore, this study aims to examine the impact of melatonin in conjunction with physical activity in breast cancer survivors (BCS).MethodsParticipants were postmenopausal women (60–75 years old) who had been diagnosed with stage I-III breast cancer 5 years ago and had received chemotherapy or radiotherapy. Participants were randomly assigned to two groups: experimental group (MEL) (n = 10), which received melatonin supplementation (6 mg/day), and the control group (CG) (n = 10), which received a placebo. Both groups followed an adapted physical activity program. After 10 weeks, body composition, physical condition, health-related quality of life and hormonal pattern were assessed in a randomized, single-blind, placebo-controlled trial (Clinical Trials.gov ID NCT06696378) following the Consolidated Standards of Reporting Trials. A Two-way repeated-measures analysis of variance (ANOVA) was used to examine the interaction effects (time × group) between MEL and CG. A significance level of p < 0.05 indicated a statistically significant difference.ResultsAfter 10 weeks, both groups showed a non-significant decrease (p > 0.05) in fat mass. Both MEL and CG exhibited a significant reduction (p < 0.05) in the Borg Rating of Perceived Exertion (RPE) when comparing the beginning (T1) and end (T2) of the study Additionally, statistically significant differences (p = 0.018) were observed overtime between T1 and T2 in the MEL and CG in RPE, with a moderate effect size (η2p = 0.347). On the other hand, the Quality-of-Life Questionnaire (four domains and total score) and Short Physical Performance Battery indicated no significant (p > 0.05) differences between MEL and CG. Finally, testosterone/cortisol ratio decreased in both groups at the end of intervention, but the difference was not statistically significant (p > 0.05).ConclusionsMelatonin supplementation (6 mg/day) for 10 weeks, combined with a physical activity program, had not significant (p > 0.05) effects on anthropometry, physical condition, health-related quality of life and hormonal response compared to the placebo group. Our findings suggest no clear effect of melatonin in post-treatment for BCS in the mentioned parameters. Further clinicals trials are recommended to establish definitive recommendations for physical activity and melatonin supplementation in BCS.Clinical Trial RegistrationClinical Trials.gov, identifier (NCT06696378).